Metode Dakwah Nahdlatul Ulama dan Muhammadiyah dalam Percepatan Vaksinasi Covid-19 di Jawa Timur - Fathiyah Khasanah Arrahmah; Angger Bimantara; Imam Alif Hidayat; Evi Merdika Listiani; Moh Ali Aziz; Sokhi Huda (Alhadharah: Jurnal Ilmu Dakwah, 2022)
This study aims to explain the Nahdlatul Ulama and Muhammadiyah Da'wah Methods in accelerating COVID-19 vaccination in East JavaThis research is qualitative research using data collection tools through interviews, documentation and observations from related parties. This research is based on data that East Java is the region with the highest COVID-19 vaccine achievement in Indonesia and the involvement of Nahdlatul Ulama and Muhammadiyah in this achievement. The results of this study indicate that Nahdlatul Ulama and Muhammadiyah use the da'wah qudwah hasanah and da'wah bi al ḥāl methods in the process of accelerating the COVID-19 vaccination. The qudwah hasanah da'wah is carried out by publishing the figures of their respective organizations when carrying out COVID-19 vaccination activities as a form of qudwah or examples for their respective members. As for the da'wah bill with the implementation of COVID-19 vaccination in several places and educational institutions of Nahdlatul Ulama and Muhammadiyah, besides that Muhammadiyah also formed a special agency called MCCC (Muhammadiyah COVID-19 Command Center). From these various activities, the two organizations contributed to the success of achieving the COVID-19 vaccination target in East Java.